Relation of elevated serum ferritin levels to hypothyroidism in children with beta-thalassemia major - Kundu, Dipankar; Ray, Debes; Ghosh, Srinika; Gon Chowdhury, Debkanya; Dutta, Suparna; Dhar, Aninda (International Journal of Medical Research and Review, 2016)
Background: The commonest form of thyroid dysfunction, seen in thalassaemics, is subclinical hypothyroidism due to abnormalities of the thyroid gland which, leads to insufficient production of thyroid hormones. However, the frequency of hypothyroidism varies depending on the region, quality of management and treatment protocols. Aim: This study was conducted with the aim of investigating the frequency of hypothyroidism in children with beta-thalassemia major and to study its correlation with serum ferritin. Material and methods: A case-control study was carried out in the OPD, Medical College, Kolkata. It included 100 children with Beta–Thalassemia major as cases. Hundred age and gender matched healthy controls were also included in the study. Results: The weight and height of the cases lagged behind those of the control group. Compared to the control group, the mean level of thyroid hormones (both T3 and T4) and Hemoglobin levels were significantly reduced while those of TSH and Serum Ferritin were significantly increased. Out of 100 cases, 64 were euthyroid, 34 and 2% had subclinical and clinical hypothyroidism respectively. No case of secondary hypothyroidism was detected. Our results showed no association between Serum ferritin levels and the frequency of hypothyroidism among studied patients. Conclusion: Thyroid dysfunction in thalassemia may start early in life, hypothyroidism is not clinically observed in most thalassemia major patients. Therefore, thyroid function should be followed on regular basis when other iron over load associated complications occurs. Regular follow-up for early detection and timely treatment of such complications could improve the quality of life of these patients.